Challenges and advances in wide-temperature rechargeable lithium batteries - Feng, Yang; Zhou, Limin; Ma, Hua; Wu, Zhonghan; Zhao, Qing; Li, Haixia; Zhang, Kai; Chen, Jun (Energy & environmental science, 2022)
Rechargeable lithium batteries (RLBs), including lithium-ion and lithium-metal systems, have recently received considerable attention for electrochemical energy storage (EES) devices due to their low cost, sustainability, environmental friendliness, and temporal and spatial transferability. Most RLBs are harnessed only in favourable environments rather than extreme climates/conditions such as ocean exploration, tropical areas, high altitude drones, and polar expeditions. When chronically or periodically exposed to harsh environments, conventional RLBs will fail to work, especially in low- and high-temperature zones ( i.e. , below 0 °C and above 60 °C). Constructing alternative electrode materials and electrolyte systems with strong temperature tolerance lays the foundation for developing full-climate RLBs. Herein, the key stumbling blocks to realizing wide-temperature RLBs are first comprehensively discussed. Then the latest research progress to address the challenges at extreme temperatures is gradually introduced. And the fundamental operating mechanism and design strategies of electrolyte and electrode materials for RLBs working within a wide-temperature range are reviewed in detail. Finally, insights into and perspectives on energy materials and battery systems are provided to develop wide-temperature-operating range energy storage devices. Building rechargeable lithium batteries for wide-temperature applications requires us to investigate the battery failure mechanism at low/high temperature, design advanced electrode/electrolyte materials, and optimize the battery management system.